PROSPECT OF SEA CUCUMBER CULTURE IN INDONESIA AS POTENTIAL FOOD SOURCES - Henneke Pangkey; Sartje Lantu; Lusia Manuand; JeffrieFredrik Mokolensang (JOURNAL OF COASTAL DEVELOPMENT, 2012)
Sea cucumber is one of the sea treasures which has been used not only as luxury food for certain countries but also as medicines. Sea cucumber has become one of the most important products and it has high price in international market.For this reason, the exploitation of sea cucumber turns out to be excessive and disturbs its sustainability. Aquaculture is the best way to prevent this problem. The success of sea cucumber culture is very depend on seed availability and suitable food for larvae as well as juvenile along with growing out stadia for market requirement.